2016
DOI: 10.3390/medicines3020015
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome and Framingham Risk Score: Observation from Screening of Low-Income Semi-Urban African Women

Abstract: Background: The heightened cardiovascular risk associated with metabolic syndrome (MetS) has been documented by several researchers. The Framingham risk score (FRS) provides a simple and efficient method for identifying individuals at cardiovascular risk. The objective was to describe the prevalence of MetS and its association with FRS in predicting cardiovascular disease among a cohort of semi-urban women; Method: Clinical and laboratory parameters were evaluated among 189 healthy women. The International Dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 48 publications
0
6
0
1
Order By: Relevance
“…The standardized prevalence rate of MetS in Kazakhs was 28.61%, which was much higher than the national MetS prevalence rate of 16.5% [ 24 ]. Studies have shown that individuals with MetS are more likely to develop CVD [ 25 , 26 ], and a higher prevalence of MetS suggests that the risk of developing CVD in the Kazakh population may be higher.…”
Section: Discussionmentioning
confidence: 99%
“…The standardized prevalence rate of MetS in Kazakhs was 28.61%, which was much higher than the national MetS prevalence rate of 16.5% [ 24 ]. Studies have shown that individuals with MetS are more likely to develop CVD [ 25 , 26 ], and a higher prevalence of MetS suggests that the risk of developing CVD in the Kazakh population may be higher.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have suggested that MS is a cluster of CVD risk factor [15][16][17][18] . A meta-analysis by Mottillo et al [19] .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous previous studies found that MS is a risk factor for CVD[ 5 , 6 , 18 21 ]. Our investigation also showed that MS is associated with CVD and this association persisted even after the adjustment for sex, drinking history, family history of hypertension, family history of diabetes, and family history of CVD.…”
Section: Discussionmentioning
confidence: 99%